2021
DOI: 10.3390/en14030784
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Method for Modeling of Pressure Losses and Heat Transfer in Fixed-Bed Reactors with Low Tube-to-Particle Diameter Ratio

Abstract: This manuscript presents a simplified method of modeling fixed-bed reactors based on the porous medium. The proposed method primarily allows the necessity of precisely mapping the internal structure of the bed—which usually is done using real object imaging techniques (like X-ray tomography) or numerical methods (like discrete element method (DEM))—to be avoided. As a result, problems with generating a good quality numerical mesh at the particles’ contact points using special techniques, such as by flattening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The article [3] entitled "A Simplified Method for Modeling of Pressure Losses and Heat Transfer in Fixed-Bed Reactors with Low Tube-to-Particle Diameter Ratio" focuses on modeling fixed bed reactors using porous models. The proposed simplified methodology showed that complicated methods of mapping the internal structure of the bed can be avoided.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%
“…The article [3] entitled "A Simplified Method for Modeling of Pressure Losses and Heat Transfer in Fixed-Bed Reactors with Low Tube-to-Particle Diameter Ratio" focuses on modeling fixed bed reactors using porous models. The proposed simplified methodology showed that complicated methods of mapping the internal structure of the bed can be avoided.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%